PENGARUH INVESTMENT DECISION, PROFITABILITY, DAN FAKTOR LAIN TERHADAP FIRM VALUE - Winda, Winda; Jonathan, Aries (E-Jurnal Akuntansi TSM, 2024)
The increasing performance of the firm is one of the interests of investors in investing. The value of a firm is reflected in its share price which continues to increase in the long term. The higher the share price, the higher the firm value. The purpose of this study is to obtain empirical evidence about the effect of dividend policy, investment decision, leverage, profitability, firm size, current ratio, managerial ownership, and total assets turnover on firm value. The object of this study are consumer cyclicals and non-cyclicals companies listed on the Indonesia Stock Exchange from year 2020 until year 2022. The selection sample in this study used purposive sampling method with a total 105 data samples used. This study used a multiple regeression in analyzing the data. The results of this study indicate that leverage, profitability, investment decision, and managerial ownership affect firm value. Leverage has a positive effect on firm value, the use of debt as a source of funding can optimize the company's operational activities to obtain the benefits that the company wants to achieve so that it can increase the firm value. Profitability has a positive effect on firm value, high level of profitability will attract investors to invest so that it can increase the firm value. Investment decision has a negative effect on firm value, inappropriate investment decisions can affect the development of a company’s business so that can reduce investor confidence and decrease the firm value. Managerial ownership has a negative effect on firm value, high managerial ownership will make management make decisions only to prosper the interests of management in decision making, so that investors do not have maximum control and decrease the firm value. Meanwhile, the dividend policy, firm size, current ratio, and total assets turnover have no effect on firm value.